A Dialogic Approach to Supervision in the Practicum - M'Balia Thomas (The Advocate, 2016)
T​he term “dialogue” in research on classroom talk between student(s)-teacher is frequently referenced in teaching and teacher education. Yet, there is considerable difference in how the concept is understood. Moreover, scholarship within this area rarely addresses classroom talk between another student-teacher dyad – that of practicum student and a supervising instructor (Waite 1995 is a notable exception). This paper seeks to explore the notion of dialogue as it applies to this dyadic relationship, considering the ways in which incorporating a specifically Bakhtinian approach to dialogue highlights unique aspects of talk and interaction within practicum supervision.